Deep brain stimulation as a rescue for pediatric dystonic storm. Case reports and literature review - Aisha Alkubaisi (17380441) (2022)
Introduction Dystonic storm is a life-threatening condition that can cause rhabdomyolysis, respiratory failure and has a high mortality rate (10–15%). It occurs in primary or secondary dystonia and can be triggered by infection, drug withdrawal or a surgical procedure. Patients have severe dystonic muscle contractions and require hospitalization with an escalation of treatment including medically induced coma. When all medical treatments fail, surgery is indicated. Case presentation We present two paediatric cases of dystonic storm with successful deep brain stimulation (DBS) rescue and highlight the diagnosis, surgery, and neuromodulation parameters. A 10-year-old boy with secondary dystonia due to a GNAO1 gene mutation developed dystonic storm and was admitted to the pediatric intensive care unit (PICU) for 60 days. His muscle spasms were refractory to clonidine and clonazepam, and he required sedation with a midazolam infusion in combination with ketamine, dexmedetomidine and clonidine. Bilateral pallidal DBS was performed under GA and he was discharged home after ten days. His Pediatric Barry Albright Dystonia score (0–30, lower scores better) improved from 27 to 1. A 7-year-old girl with dystonic storm secondary to cerebral palsy was admitted to the PICU for 14 days and sedated with a ketamine infusion with dexmedetomidine and clonidine. She had bilateral GPi DBS and was discharged from the PICU after ten days. Her score improved from 28 to 17. The surgical targeting and stimulation parameters will be presented. Conclusion Pallidal DBS should be considered in children with medically refractory dystonic storm. This paper also highlights the stimulation parameters required for DBS rescue which has not been previously discussed in the literature. Other Information Published in: Interdisciplinary Neurosurgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.inat.2022.101654